Defect Detection in Anisotropic Plates Based on the Instantaneous Phase of Signals - Prado, Vander Teixeira; Garcia Granja, Silvio Cesar; Higuti, Ricardo Tokio [UNESP]; Kitano, Claudio [UNESP]; Martinez-Graullera, Oscar; Elvira Segura, Luis (Ieee-inst Electrical Electronics Engineers Inc, 2015)
Anisotropic materials are widely employed in industry and engineering, and efficient nondestructive testing techniques are important to guarantee the structural integrity of the involved parts. A simple technique is proposed to detect defects in anisotropic plates using ultrasonic guided waves and arrays. The technique is based on the application of an objective threshold to a synthetic aperture image obtained from the instantaneous phase (IP) of the emitter-receiver signal combinations. In a previous work the method was evaluated for isotropic materials, and in this paper it is shown that with some considerations the technique can also be applied to anisotropic plates. These considerations, which should be taken into account in beamforming, are (1) group velocity dependence with propagation direction, and (2) elastic focusing, which results in energy concentration in some propagation directions, with the practical consequence that not all aperture signals effectively contribute to the image. When compared with conventional delay-and-sum image beamforming techniques, the proposed IP technique results in significant improvements relative to defect detection and artifacts/dead zone reduction.